Lipid regulation of BK channel function - Dopico, Alex M.; Bukiya, Anna N. (Frontiers in Physiology, 2014)
This mini-review focuses on lipid modulation of BK (MaxiK, BKCa) current by a direct interaction between lipid and the BK subunits and/or their immediate lipid environment. Direct lipid-BK protein interactions have been proposed for fatty and epoxyeicosatrienoic acids, phosphoinositides and cholesterol, evidence for such action being less clear for other lipids. BK α (slo1) subunits are sufficient to support current perturbation by fatty and epoxyeicosatrienoic acids, glycerophospholipids and cholesterol, while distinct BK β subunits seem necessary for current modulation by most steroids. Subunit domains or amino acids that participate in lipid action have been identified in a few cases: hslo1 Y318, cerebral artery smooth muscle (cbv1) R334,K335,K336, cbv1 seven cytosolic CRAC domains, slo1 STREX and β1 T169,L172,L173 for docosahexaenoic acid, PIP2, cholesterol, sulfatides and cholane steroids, respectively. Whether these protein motifs directly bind lipids or rather transmit the energy of lipid binding to trigger protein conformation change remains unresolved. The impact of direct lipid-BK interaction on physiology is briefly discussed.